(3eSFhdjI QFjS GdOhdI ai Gdabg GdGSdGei (B:s (3OQGSI ebGQfI HGdfXGe GdOSJhQi GdeUQi (B/ s - (3eMeO ahRi dWja fhjLis; (3GfhQ eMehO OHhQ s; (3eMeO MSfjf YHOGdYGd s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2002)
(3JYJHQ GdeSFhdjI GdOQY GdhGbj ef WZjGf GdSdWI , h GdeSFhdjI JJbQQ aj MGdI hLhO Lh OjebQGWj jHGM ajg eSGFdI CYdi aQO aj GdeLJeY, gPg GdeSFhdjI JMJGL Edi eRjO ef GdLghO ef bHd GdeTQY GdOSJhQj dJfXjegG HfUhU LOjOI dcj jJe JbQjQgG aj UdH GdOSJhQ dCfg de jJbQQ Shi fhY hGMO efgG aj GdOSJhQ GdeUQj MJi GdBf h gj GdeSFhdjI GdLfGFjI h GdJj JMJGL UOhQ bGfhf jfXegG(B. (3h Ydi LGfH BNQ jeKd GdfXGe GdESdGej Hjf CfXeI GdMce aj GdYGde CaVd GdCfXeI Ydi GdEWdGb aj eLGd eSFhdjI QFjS GdOhdI(B. (3MjK bQQgG HfUhU bGWYI aj TJi eLGdGJ GdSdWI h de jZad LGfH efgG ceG aYdJ GdbhGfjf GdhVYjI aj gPG GdTCf h eG CKjQ Mhd gPG GdehVhY ef GaJQGAGJ eG gj EdG eMGhdGJ dJThjg UhQI GdESdGe aj TCf fXGe GdMce h NUhUG(B" (3eSFhdjI QFjS GdOhdI(B.s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2002s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B641-682s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdabI GdGSdGeis; (3bGfhf YGes; (3eSFhdjI QFjS GdOhdIs; (3JbQjQ GdeSFhdjIs; (3fTCI GdeSFhdjI aj GdbGfhf GdhVYj hGdESdGes; (3eUGOQ GdeSFhdjIs; (3CSHGH eSFhdjI QFjS GdOhdI aj GdOSJhQ GdeUQj hGdabg GdESdGejs; (3GSS GdeSFhdjI s; (3CKGQ GdeSFhdjI aj GdOSJhQ GdeUQj hGdabI GdESdGejs; (3GdLgI GdJj JbQQ GdeSFhdjI hGdeMeI GdeNJUIs; (3fWGb GdeSFhdjI hGKGQgGs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes